I materiali ceramici trasparenti: preparazione, caratterizzazione e correlazione microstruttura-proprietà - Esposito, Laura <1965> (Alma Mater Studiorum - Università di Bologna, 2011)
This thesis focuses on the ceramic process for the production of optical grade transparent materials to be used as laser hosts. In order to be transparent a ceramic material must exhibit a very low concentration of defects. Defects are mainly represented by secondary or grain boundary phases and by residual pores. The strict control of the stoichiometry is mandatory to avoid the formation of secondary phases, whereas residual pores need to be below 150 ppm. In order to fulfill these requirements specific experimental conditions must be combined together. In addition powders need to be nanometric or at least sub-micrometric and extremely pure. On the other hand, nanometric powders aggregate easily and this leads to a poor, not homogeneous packing during shaping by pressing and to the formation of residual pores during sintering. Very fine powders are also difficult to handle and tend to absorb water on the surface. Finally, the powder manipulation (weighting operations, solvent removal, spray drying, shaping, etc), easily introduces impurities. All these features must be fully controlled in order to avoid the formation of defects that work as scattering sources thus decreasing the transparency of the material. The important role played by the processing on the transparency of ceramic materials is often underestimated. In the literature a high level of transparency has been reported by many authors but the description of the experimental process, in particular of the powder treatment and shaping, is seldom extensively described and important information that are necessary to reproduce the described results are often missing. The main goal of the present study therefore is to give additional information on the way the experimental features affect the microstructural evolution of YAG-based ceramics and thus the final properties, in particular transparency. Commercial powders are used to prepare YAG materials doped with Nd or Yb by reactive sintering under high vacuum. These dopants have been selected as the more appropriate for high energy and high peak power lasers. As far as it concerns the powder treatment, the thesis focuses on the influence of the solvent removal technique (rotavapor versus spray drying of suspensions in ethanol), the ball milling duration and speed, suspension concentration, solvent ratio, type and amount of dispersant. The influence of the powder type and process on the powder packing as well as the pressure conditions during shaping by pressing are also described. Finally calcination, sintering under high vacuum and in clean atmosphere, and post sintering cycles are studied and related to the final microstructure analyzed by SEM-EDS and HR-TEM, and to the optical and laser properties.